2002
DOI: 10.1536/jhj.43.117
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Brachial Artery Flow Mediated Dilation and Carotid Artery Intima-Media Thickness in Patients with Suspected Coronary Artery Disease.

Abstract: SUMMARYThe correlation of peripheral endothelial dysfunction and intima-media thickness (IMT) in patients with suspected coronary artery disease (CAD) has been unclear. Inflammation and thrombosis may play a role at early stages of atherosclerosis. Thus, early atherosclerosis was noninvasively examined morphologically by IMT of carotid arteries, and functionally by flow mediated dilation (FMD) of brachial arteries in patients who were suspected of CAD and had undergone coronary angiography. Plasma antigen leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 25 publications
0
36
2
Order By: Relevance
“…The majority of studies to date that have examined the relationship between BFMD and anatomical measures of atherosclerosis have tended to focus on men or populations without clinical CVD. Correlations between BFMD and IMT reported by these studies ranged from r = −0.21 to −0.41 [13,[15][16][17], which are of greater magnitude than we observed (r = −0.12). Our findings in women with mild to moderate CAD provide support that the relationship between BFMD and anatomical measures of atherosclerosis holds true in women and among those with CAD, albeit at a lower magnitude than previously reported.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…The majority of studies to date that have examined the relationship between BFMD and anatomical measures of atherosclerosis have tended to focus on men or populations without clinical CVD. Correlations between BFMD and IMT reported by these studies ranged from r = −0.21 to −0.41 [13,[15][16][17], which are of greater magnitude than we observed (r = −0.12). Our findings in women with mild to moderate CAD provide support that the relationship between BFMD and anatomical measures of atherosclerosis holds true in women and among those with CAD, albeit at a lower magnitude than previously reported.…”
Section: Discussioncontrasting
confidence: 65%
“…While QCA and CIMT are associated with prevalent CVD and have strong prognostic value for incident CVD independent of risk profiles [1,3,[6][7][8][9], the diagnostic and prognostic importance of BFMD for CVD is less certain [10]. Although some studies have shown BFMD to be predictive of future coronary events [11,12], only a handful of studies have reported an inverse association between BFMD and CIMT [13][14][15][16][17][18]. The majority of these studies were small, cross-sectional evaluations of men with pre-existing coronary artery disease (CAD) [13,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelium-dependent vasodilatation is realized through vasodilator agents such as NO. Abnormal NO activity is linked to atherosclerosis and vasculopathy [20]. The changes in NO levels may be determined through the measurement of the nitrite/nitrate levels in the plasma or indirectly through a non-invasive technique such as FMD measurement [21].…”
Section: Discussionmentioning
confidence: 99%
“…Carotid intima-media thickness (CIMT), flow associated dilatation (FAD %) and nitric oxide sensitivity of the smooth muscle cell of the brachial artery to nitroglycerine (GTN %) are legitimate markers of early atherosclerosis (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). CIMT is a surrogate marker for generalized atherosclerosis and imparts prognostic information independent of traditional cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%